2008
DOI: 10.1039/b804236e
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependent Stokes drag in a colloidal liquid crystal

Abstract: Stokes drag on the (sub)micrometre scale plays a key role in phenomena ranging from Brownian motion to the rheology of particulate suspensions. We report the first measurement of the direction dependent Stokes drag in a nematic liquid crystal of colloidal rods, where the viscous forces are of equal importance to the elastic forces. By tracking a sedimenting sphere with combined fluorescence confocal microscopy and polarization microscopy we find that the Stokes drag for motion along the director is two times l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…It was found that the ratio between the viscosities becomes much smaller in this case, and the defect structure changes, e.g. from a Saturn ring to a dipole [5,6].…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It was found that the ratio between the viscosities becomes much smaller in this case, and the defect structure changes, e.g. from a Saturn ring to a dipole [5,6].…”
mentioning
confidence: 86%
“…It was found that the ratio between the viscosities becomes much smaller in this case, and the defect structure changes, e.g. from a Saturn ring to a dipole [5,6].Here we consider the hydrodynamics of a colloidal particle (radius R) inside a cholesteric liquid crystal, which differs from the nematic by having a helical twist to the director field with a pitch p. (This additional order breaks translational as well as rotational symmetry. )We focus on the case of tangential anchoring in which the director field at the colloid-fluid interface lies everywhere parallel to the surface of the particle.…”
mentioning
confidence: 99%
“…The Stokes drag is highly nonlinear for particles in a nematic solvent; the colloid (acting as a quadrupole) finds it easier to diffuse parallel ton than perpendicular to it [24,25]. Further research by Verhoeff et al [26] quantized this direction-dependent Stokes drag. They demonstrated that, for a colloid moving through a nematic LC, the viscous drag (VD) parallel ton was larger than the drag perpendicular ton by a factor of 2.…”
Section: Anisotropic Viscosity In Liquid Crystalsmentioning
confidence: 99%
“…This fact also becomes apparent when comparing our results to the anisotropy in tracer motion as observed in bulk nematics. 40,41 In the case of the long fibrils, the aspect ratio between the probe particles and the anisotropic objects is reversed compared to bulk nematics. As a consequence of this, the observed anisotropy in tracer motion is much higher than that observed for small molecules or short rods in bulk.…”
mentioning
confidence: 99%